PENGARUH EKSPOR TANAMAN OBAT, KURS, DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Anggia Putri; Devi Andriyani (LPPM Universitas Malikussaleh – Indonesia, 2022)
This study aims to see the effect of crop exports, exchange rates and inflation on economic growth in Indonesia. The data used in this research is time series data from 2012 to 2019. The research method uses multiple regression analysis. The results of the study partially show that the export of medicinal plants has no significant effect on economic growth in Indonesia, the exchange rate has no significant effect on economic growth in Indonesia, and inflation has no significant effect on economic growth in Indonesia. Simultaneously, the export of medicinal plants, exchange rates and inflation have a positive and significant effect on economic growth in Indonesia and have an effect shown by the coefficient of determination (R2) of 87.09% which indicates that the variable plant exports, exchange rates and inflation can explain the variable Y, while 12.91% assumptions by other variables outside the research variables